The Three Lipocalins of Egg-White: Only Ex-FABP Inhibits Siderophore-Dependent Iron Sequestration by Salmonella Enteritidis - Julien, Louis Alex; Fau, Clémence; Baron, Florence; Bonnassie, Sylvie; Guérin-Dubiard, Catherine; Nau, Françoise; Gautier, Michel; Karatzas, Kimon Andreas; Jan, Sophie; Andrews, Simon Colin (Frontiers in Microbiology, 2020)
Salmonella Enteritidis is the most prevalent food-borne pathogen associated with egg-related outbreaks in the European Union. During egg colonisation, S. Enteritidis must resist the powerful anti-bacterial activities of egg white (EW) and overcome ovotransferrin-imposed iron-restriction (the most important anti-bacterial mechanism of EW). Many pathogens respond to iron restriction by secreting iron-chelating chemicals called siderophores but EW contains a siderophore-sequestering ‘lipocalin’ protein (Ex-FABP) that is predicted to limit the usefulness of siderophores in EW. S. Enteritidis produces two siderophores: enterobactin, which is strongly bound by Ex-FABP; and the di-glucosylated enterobactin-derivative, salmochelin (a so-called ‘stealth’ siderophore), which is not recognised by Ex-FABP. Thus, production of salmochelin may allow S. Enteritidis to escape Ex-FABP-mediated growth inhibition under iron restriction although it is unclear whether its EW concentration is sufficient to inhibit pathogens. Further, two other lipocalins (Cal-γ and α-1-ovoglycoprotein) are found in EW but their siderophore sequestration potential remains unexplored. In addition, the effect of EW lipocalins on the major EW pathogen, S. Enteritidis, has yet to be reported. We overexpressed and purified the three lipocalins of EW and investigated their ability to interact with the siderophores of S. Enteritidis, as well as their EW concentrations. The results show that Ex-FABP is present in EW at concentrations (5.1 µM) sufficient to inhibit growth of a salmochelin-deficient S. Enteritidis mutant under iron restriction but has little impact on the salmochelin-producing wildtype. Neither Cal-γ or α-1-ovoglycoprotein bind salmochelin or enterobactin, nor do they inhibit iron-restricted growth of S. Enteritidis. However, both are present in EW at significant concentrations (5.6 and 233 µM, respectively) indicating that α-1-ovoglycoprotein is the 4th most abundant protein in EW, with Cal-γ and Ex-FABP at 11th and 12th most abundant. Further, we confirm the preference (16-fold) of Ex-FABP for the ferrated form (Kd of 5.3 nM) of enterobactin over the iron-free form (Kd of 86.2 nM), and its lack of affinity for salmochelin. In conclusion, our findings show that salmochelin production by S. Enteritidis enables this key egg-associated pathogen to overcome the enterobactin-sequestration activity of Ex-FABP when this lipocalin is provided at levels found in EW.